Vanishing the existence of the mandible? - Narayan Dutt Pandey; Shrikant Dusane; Bhushan Ramdas Bhagat; Shubhangi Bhushan Bhagat (Wolters Kluwer Medknow Publications, 2023)
Phantom bone disease, also known as Gorham's disease, is a rare disorder characterized by the progressive destruction of one or more skeletal bones. Commonly involved bones are the upper and lower extremities. Very few cases have been reported in the maxillofacial region with unilateral mandible being commonly involved. This case, to our knowledge, is the third case of Gorham's disease involving the whole length of the mandible in a 55-year-old female with a brief discussion on its clinical, radiographic, and histopathological presentation and treatment options.